Respuesta :

first convert the radicals to fractional indices:-

= [ ( a^9 b^3)1/4]^1/3

= (a^9 b^3)^1/12

= a^3/4 b^1/4 answer

to the risk of sounding a bit redundant.


[tex] \bf a^{\frac{ n}{ m}} \implies \sqrt[ m]{a^ n}
\qquad \qquad
\sqrt[ m]{a^ n}\implies a^{\frac{ n}{ m}}\\\\
------------------------------- [/tex]


[tex] \bf \sqrt[3]{\sqrt[4]{a^9b^3}}\implies \sqrt[3]{(a^9b^3)^{\frac{1}{4}}}\implies \left[ (a^9b^3)^{\frac{1}{4}} \right]^{\frac{1}{3}}\implies (a^9b^3)^{\frac{1}{4}\cdot \frac{1}{3}}
\\\\\\
(a^9b^3)^{\frac{1}{12}}\implies a^{9\cdot \frac{1}{12}}b^{3\cdot \frac{1}{12}}\implies a^{\frac{3}{4}}b^{\frac{1}{4}}\implies \sqrt[4]{a^3}\cdot \sqrt[4]{b^1}
\\\\\\
\sqrt[4]{a^3b^1}\implies \sqrt[4]{a^3b} [/tex]